Development of a Web-Based Information System for Smartphone Repair Services at OSDIG Store Using the Waterfall Method - Umar, Rusydi; Ahnafi, Muhammad Ghazi (Innovation, Technology, and Entrepreneurship Journal, 2025)
The advancement of information technology compels small and medium-sized enterprises (SMEs), particularly in service sectors, to adopt digital solutions to improve operational efficiency. OSDIG Store, a smartphone repair service specializing in Apple devices, faces several issues, including manual service tracking, inefficient data management, and lack of structured inventory and financial records. This study aims to develop a web-based information system tailored to the operational workflow of OSDIG Store. The system was built using the Waterfall development methodology, which includes requirements analysis, system design, implementation, and testing. Key features developed include customer data management, repair tracking, inventory control, and transaction logging. Functional testing was conducted using the Black Box method, while user experience evaluation utilized the User Experience Questionnaire (UEQ). The test results indicate that the system meets functional requirements and delivers positive user experience scores in attractiveness and efficiency dimensions. The implementation of this system streamlines daily operations, reduces service errors, and improves transparency between service providers and customers. This research contributes a practical software solution for SMEs in the service sector and demonstrates the applicability of structured software engineering practices in real-world microbusiness contexts.